Depressive symptoms in postpartum women at Family Health Units - Synara Barbosa de Melo; Rhayza Rhavênia Rodrigues Jordão; Fernanda Jorge Guimarães; Jaqueline Galdino Albuquerque Perrelli; Amaury Cantilino; Everton Botelho Sougey
Abstract Objectives: to identify postpartum depression among women assisted by Family Health Units (FHU). Methods: this is a cross-sectional study with a quantitative approach carried out in FHUs at the city of Vitoria de Santo Antão - PE. Fifty eight mothers constituted the sample. We used the Portuguese version of the Postpartum Depression Screening Scale - PDSS for screening. We collected data from February to April 2011. Results: we were able to demonstrate that 8.6% of participants had scores above the PDSS cut-off point. We also found an association between postpartum depression and incomplete primary education. Conclusions: although the percentage of women with postpartum depression scores is lower than values found in other national studies, the early identification of these mothers in FHU is imperative, given the harmful repercussions that depression can cause in women, as well as in physical and psychic development of the baby.